(untitled) (Práxis Educativa, 2018)
This paper deals with the results of a critical review of Brazilian Postgraduate production about the participation of young students in High School. Thirty nine thesis and dissertations produced between 2005 and 2017 in the areas of Education, Social Sciences and Psychology in Brazil were identified, among them 25 texts were fully recovered and constituted the corpus of the research. The theoretical framework used was the Sociology of Youth and Educational studies. The data indicate a production that increased after the first decade, although there are still several gaps to be developed due to the recent expansion of High School and the new forms of contemporary collective actions. Keywords: High school. Youth. Participation.